Molecular Study of Cysticercus Tenuicollis from Slaughtered Sheep in Sulaymaniyah Province, Iraq - Mohammed, Aram Ahmad (J Vet Res, 2020)
INTRODUCTION: Cysticercosis caused by the larval stage of Taenia hydatigena is economically the most important endemic parasitic disease in Iraq. Few data are available relating to the genetic divergence of this helminth. This study aimed to molecularly characterise Cysticercus tenuicollis isolates from sheep in Sulaymaniyah province, Iraq. MATERIAL AND METHODS: DNA extraction and amplification of specimens of C. tenuicollis from 46 sheep were conducted by PCR for the mitochondrial 12S rRNA gene. The 19 amplicons were subjected to purification and partial sequencing. RESULTS: Five 12S rRNA nucleotide sequence haplotypes were found. The pairwise nucleotide difference between haplotypes of 12S rRNA gene ranged from 0.2% to 0.7%. Four out of the five haplotypes of C. tenuicollis contained one to two base mutations and were discovered in Iraq for the first time, and this may be a unique mutation globally which has not been recorded previously. Three newly recorded haplotypes contained only one single mutation, and the other one contained two mutations. Phylogenetic analysis showed that all isolated strains were closely related to Iranian sheep isolates. CONCLUSIONS: Four new strains of T. hydatigena were discovered for the first time in the study area.